PERSEPSI MASYARAKAT TERHADAP KEBERADAAN OBJEK EKOWISATA MANGROVE DI DESA PASIR KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Mayangsari, Dian; Muin, Sudirman; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2017)
This research aims at finding out society’s perception and the correlation of the society’s perception towards mangrove eco-tourism existance in in Pasir village Mempawah sub-district Mempawah Regency about their income level, the number of their family dependents, the level of their dependence as well as their knowledge level toward mangrove. The descriptive result showed about the society’s perception on thier increased revenue that there were 84 respondents, in which (17,86%) or 15 respondent stated their perception that they had gained their increased revenue, (58,33%) or 49 respondents had not gained their increased revenue yet and (23,81%) or 20 respondents did not gain their increased revenue. The Society’s perception showed based on jobfield that 84 respondents, in which (29,76%) or 25 respondents stated that the existance of the mangrove eco-tourism had created jobfields, (53,57%) or 45 respondents stated it had not created the jobfields yet and (16,67%) or 14 respondents stated it did not create the jobfields. The society’s perception showed about business opportunity that 84 responden, in which (14,29%) or 12 respondent stated that it had provided business opportunity, (72,62%) or 61 respondent stated it had not provided it yet and (13,10%) or 11 respondents stated it did not provide it. It proved that the existance of the mangrove eco-tourism had not provided positive impact towards the society about their inome, jobield as well as business opportunity. The resulting study showed that the society’s perception towards between the income level and the number of family dependents had no significant correlation, which means they had no effect on the society’s perception to the existance of the mangrove eco-tourism. The society’s perception to the level of their dependence and their knowledge level, however, had a significant correlation, meaning that they provided a significant effect to the society about their perception towards the existance of the mangrove eco-tourism.Keywords: Existance, Mangrove eco-tourism, Perception.